Penerapan Konsep Penjumlahan dalam Pembelajaran Matematika Sekolah Dasar - Amanda Oktavia Damaryanti; Denis Tri Hapsari; Unik Chanifar Rusliyati; Nieva Oktavia Saputri; Alfia Nur Wahyuningtyas (Prosiding Konferensi Ilmiah Dasar, 2026)
Learning addition is one of the basic mathematics subjects that elementary school students must master because it serves as a foundation for learning other arithmetic operations. However, students still have difficulty understanding the concept of addition due to the abstract nature of the material and the lack of appropriate teaching strategies. This research aims to analyze the application of the addition concept in elementary school mathematics learning thru a literature review. The study employs a literature review method by collecting and analyzing various relevant scientific articles on the addition concept, the use of concrete media, and mathematics learning strategies in elementary schools. Data analysis is conducted using content analysis techniques to identify the main findings from various studies. The results of the study indicate that the use of concrete media, active learning strategies, and contextual learning can enhance the understanding of the concept of addition, calculation skills, and student engagement. These findings indicate that learning tailored to the developmental characteristics of students can create more effective and meaningful mathematics education.